1994
DOI: 10.1002/jhrc.1240171107
|View full text |Cite
|
Sign up to set email alerts
|

Direct coupling of capillary supercritical fluid chromatography with double‐focusing high resolution mass spectrometry

Abstract: SummaryAn integral restrictor interface with jet separator for coupling capillary column supercritical fluid extraction -supercritical fluid chromatography with high resolution mass spectrometry (SFE-SFC-MS) has been built and used for the analysis of a fatty acid ester, and of polymer additives with a wide range of masses. The mobile phase used was supercritical carbon dioxide; a flame ionization detector (FID) was used in parallel with the mass spectrometer. Different SFC-MS interface operating conditions, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Cryopumping was later used to assist in the identification of high molecular weight components of olestra, a mixture of fatty acid sucrose esters (123). Buecherl et al built and tested an interface, incorporating a second restriction and a stage of pumping between the SFC restrictor and the ion source, for coupling open-tubular SFC to highresolution MS (124). The additional stage of pumping was required to maintain a sufficient vacuum in the ion source region.…”
Section: Sfc Instrumentation Techniques and Performancementioning
confidence: 99%
“…Cryopumping was later used to assist in the identification of high molecular weight components of olestra, a mixture of fatty acid sucrose esters (123). Buecherl et al built and tested an interface, incorporating a second restriction and a stage of pumping between the SFC restrictor and the ion source, for coupling open-tubular SFC to highresolution MS (124). The additional stage of pumping was required to maintain a sufficient vacuum in the ion source region.…”
Section: Sfc Instrumentation Techniques and Performancementioning
confidence: 99%
“…14 In addition, on-line SFE-cSFC-MS studies on polymer additives have been reported. 15,16 All of these applications have used capillary columns, which are capable of providing high resolution, with analysis times between 40 and 60 min. However, most polymers contain relatively few additives, and therefore the high resolving power of capillary columns is not required, and separations have been achieved in less than 10 min using pSFC.…”
Section: Introductionmentioning
confidence: 99%